Song of the Salish Sea [videorecording (DVD)] - Sefton, Nancy; Gunby, Al (Earthwise Media, 2006)
Examines the fragile habitats that make up this large inland sea and its watershed. Spectacular video of the habitats and the creatures that live there are combined with graphics, photographs and simple animations to examine these environments.